2006
DOI: 10.1128/iai.74.1.399-409.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the Staphylococcus aureus putP Gene by Low-Proline-High Osmotic Conditions and during Infection of Murine and Human Tissues

Abstract: Staphylococcus aureus can grow virtually anywhere in the human body but needs to import proline through low-and high-affinity proline transporters to survive. This study examined the regulation of the S. aureus putP gene, which encodes a high-affinity proline permease. putP::lacZ and putP::lux transcriptional fusions were constructed and integrated into the genomes of several S. aureus strains. Enzyme activity was measured after growth in media with various osmolyte concentrations. As osmolarity rose, putP exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 44 publications
0
52
1
Order By: Relevance
“…Ideally, the HKGs used in relative RT-qPCR studies are controls equally expressed under different conditions. Several HKGs have already been reported in S. aureus gene expression studies, including ftsZ [29], pta [30], hu [31], and gyrB [32]. However, previous studies have shown that the expression of the particular HKGs can be differentially regulated, depending on experimental conditions [33,34].…”
Section: Resultsmentioning
confidence: 97%
“…Ideally, the HKGs used in relative RT-qPCR studies are controls equally expressed under different conditions. Several HKGs have already been reported in S. aureus gene expression studies, including ftsZ [29], pta [30], hu [31], and gyrB [32]. However, previous studies have shown that the expression of the particular HKGs can be differentially regulated, depending on experimental conditions [33,34].…”
Section: Resultsmentioning
confidence: 97%
“…However, during growth in cheese, transcriptional stability of the reference genes differed substantially, indicating that expression has to be validated under each experimental condition (6). Each of the three genes chosen to normalize our RT-qPCR data during S. aureus growth in cheese (ftsZ, pta, and gyrB) had already been used separately in previous studies (37,41,50). We used the geometric mean of expression results using all three genes to normalize expression of our gene of interest (47).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, reference genes used in relative RT-qPCR studies are controls equally expressed under different conditions. Several housekeeping genes have already been used in S. aureus gene expression studies as single internal reference genes, including ftsZ (41), pta (37), hu (7,17,39), and gyrB (19,20,46,50). However, previous studies have shown that the expression of many housekeeping genes is differentially regulated, depending on experimental conditions (14,44).…”
mentioning
confidence: 99%
“…A mixture of wild-type and dnaK mutant cells, containing a total of 5610 8 c.f.u. ml 21 , was prepared (76/24 % mixture of mutant/wild-type) in 1 % TSB, and 0.2 ml of this suspension was injected into the peritoneal cavity of Swiss white Hla(ICR)CVF female mice (16-20 g) (Hilltop Lab Animals Inc.) with a 26 gauge needle fitted to a 1 ml syringe, following published procedures with appropriate modifications (Schwan et al, 2006). At 4, 8 and 30 h, the mice were euthanized by CO 2 asphyxiation.…”
Section: Methodsmentioning
confidence: 99%